Genesis of a Severe Dust Storm Over the Indian Subcontinent: Dynamics and Impacts. Issue 2 (2nd February 2022) - Singh, Jaydeep; Singh, Narendra; Ojha, Narendra; Srivastava, A. K.; Bisht, Deewan Singh; Rajeev, Kunjukrishnapillai; Kumar, Kiran N. V. P.; Singh, Ravi S.; Panwar, Vivek; Dhaka, S. K.; Kumar, Vinay; Nakayama, Tomoki; et al.
Abstract: The genesis, dynamics, and impacts of a severe dust storm over the central Himalaya during June 13–17, 2018 have been investigated using in situ measurements, satellite data, and model reanalysis. A low‐pressure system over northern India and prevalence of strong winds (∼20 ms −1 ) triggered the dust storm leading to poor visibility conditions and five‐fold enhancement in the fine particulate matter (PM2.5 ) over the central Himalaya. Enhancements in Aerosol Optical Depth (AOD) were observed to be stronger over the Himalayan foothills site (Lumbini) than that over the Indo‐Gangetic Plain (IGP) site‐Gandhi College. The sharp reductions in Angstrom exponent ( α ) from about 1.2 to 0.3 indicated the dominance of coarse‐mode aerosols during the dust episode. Model results show an enhancement in the dust from 1.5 to 2.5 Tg (∼70%) over the northern Indian subcontinent, with about half of the contribution from the regional source (Thar Desert). Interestingly, dust storm also had significant impacts on turbulent kinetic energy (2.9–9.6 m 2 s −2 ), vertical momentum flux (0.9–3.3 Nm −2 ), and sensible heat flux (34.8 to −33.9 Wm −2 ), suggesting turbulent mixing of aerosols and cooling near the surface over the Himalayas. Our study highlights that the large‐scale dust storms exposed to additional dust and pollution from regional sources can profoundly impact the air quality, heat fluxes, and radiative balance over the northern Indian subcontinent. The study would also help in evaluating the results of climate models and to assess the impacts of dust on the hydrological processes and melting Himalayan glaciers. Key Points: A detailed investigation on the genesis, dynamics, and impacts of a severe dust storm over northern Indian subcontinent has been conducted Analysis on the relative effects of long‐range transport and regional dust emissions affecting northern Indian subcontinent region The impacts of dust storm on characteristics of aerosols and the surface layer have been analyzed